Pelayanan Humanis Muthawif dan Tour Leader terhadap Loyalitas Jamaah Umrah dan Word of Mouth di PT Surya Madina - Kristiyuana; Lukman Hakim; Shinta Yuliana; Muhammad Habibbullah (Bayani, 2026)
Muthawif and Tour Leader (TL) services have a strategic role in supporting the smooth running of the Umrah pilgrimage, especially for elderly pilgrims who need assistance. However, the practice of Umrah services in the field is inseparable from social dynamics, such as differences in the competence of companions and the potential for inequality in the division of roles and workloads, which can affect the quality of pilgrims' services. This research aims to understand the humanist services provided by Muthawif and TL in building the experience of worship, loyalty, and word of mouth of Umrah pilgrims. This study uses a qualitative approach with a case study design on the Surya Madina Umrah bureau, involving 47 Umrah pilgrims departing on January 10, 2026. The data collection technique was carried out through observation, distribution of service assessment questionnaires, and brief interviews with pilgrims. The results of the study show that humanistic services characterized by an empathetic attitude, patience, friendliness, clarity of communication, and mentoring are able to create a sense of comfort for worshippers, increase understanding during worship, and encourage the formation of loyalty and positive word of mouth. However, this study also found that there is a dynamic division of roles and workload between Muthawif and TL which has the potential to have an impact on the physical and mental condition of officers as well as the sustainability of service quality. This study concludes that humanist services in Umrah do not only depend on the quality of empathic interaction with pilgrims, but also require proportional, professional, and sustainable management of human resources to maintain the quality of long-term services.